Application of the sustainable logistics plan in the public administration - Sales Moreira, Andréa Cristiane (Brazilian Journal of Operations & Production Management, 2018)
The Public Administration, when it consumes the natural resources in a conscious way, contributes to diminishing the negative repercussions of its activities on the environment. It is important to highlight the relevance of sustainable decisions of public managers, contributing to the achievement of positive results for the planet and the quality of life of people in the next fifteen years, supported by Agenda 2030. It is the primary objective of this study, of the constitutional principle of sustainable development - foreseen in Article 225, Brazilian Federal Constitution - and how it has been applied in the socio-environmental management of the Judicial Branch of the State of Rio de Janeiro, consistent with the assumptions of Agenda 2030, evaluating the main initiatives underway regarding the incorporation of the Goals of Sustainable Development (SDG). To this end, the stages of implementation of the Sustainable Logistics Plan (PLS) of the Rio de Janeiro State Court of Justice (TJERJ) are presented, based on exploratory and documentary research, in search for theoretical and legal support. The importance of establishing monitoring and evaluation processes was also verified, guiding the public manager in the construction of a new institutional culture in public bodies.